(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2025)
Local economies often present disparities by providing heterogeneous environments for the generation of formal businesses. The empirical analysis of business informality usually assumes a degree of homogeneity in the context of cities. This paper aims to analyze business informality based on the environmental conditions in which enterprises develop. We take the results of the Microbusiness Survey for the 13 main cities of Colombia and apply the multiplicative heteroskedastic binary model to capture the potential heterogeneity among micro businesses. Our results suggest that public policies focused on business formalization should address the differences in the environment of each microbusiness, being more likely to be formal in the case of cities with large markets and informal in environments with little incidence of government institutions.